CIRCADIAN BLOOD PRESSURE VARIABILITY AND LEFT VENTRICULAR DIASTOLIC FUNCTION IN HYPERTENSIVE MILITARY PERSONNEL: INSIGHTS FROM AMBULATORY MONITORING - Salikhov B.R.,; Alyavi A.L., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Background. Hypertension is highly prevalent among military populations and contributes to early cardiovascular remodeling. Ambulatory blood pressure monitoring (ABPM) enables detection of pathological circadian patterns strongly associated with target-organ damage.Objective. To evaluate 24-hour blood pressure parameters and circadian BP profiles in servicemen with hypertension, depending on left ventricular diastolic function.Methods. Forty-six male servicemen (mean age 45.9 ± 3.1 years) with stage I arterial hypertension (per 2018 ESC/ESH criteria) underwent echocardiography and ABPM. Patients were stratified into two groups: those with preserved diastolic function (n = 23) and those with impaired relaxation type diastolic dysfunction (n = 23).Results. Compared with patients with normal diastolic function, servicemen with diastolic dysfunction had significantly higher mean 24-h systolic BP (134.8 ± 2.1 vs 120.6 ± 1.7 mmHg, p